Matrix Metalloproteinase-2 Isoforms Differ within the Aortic Wall of Ascending Aortic Aneurysms Associated with Bicuspid Aortic Valve. (23rd September 2020) - Schmitt, Ramona; Tscheuschler, Anke; Laschinski, Philipp; Discher, Philipp; Fuchs, Jana; Kari, Fabian A.
Abstract : The pathogenesis of ascending thoracic aortic aneurysm (aTAA) is thought to differ between patients with bicuspid aortic valve (BAV) and tricuspid aortic valve (TAV), and one of the causes is different hemodynamics. Influenced by hemodynamics, the tissue levels of proteins associated with aTAA might differ between aTAAs with BAV and TAV and between different localities within the aortic wall. We therefore analyzed aTAA tissue levels of MMP-2 (matrix metalloproteinase-2) isoforms (Pro-MMP-2, active MMP-2, and total MMP-2) and tissue levels of MMP-14, TIMP-2 (tissue inhibitor of metalloproteinase-2), MMP-9, and TIMP-1 in 19 patients with BAV and 23 patients with TAV via gelatin zymography and enzyme-linked immunosorbent assay (ELISA), respectively. TAV and BAV groups' protein levels did not differ significantly. Whereas the TAV group exhibited no significant differences in protein levels between the aneurysm's anterior and posterior parts, the BAV group revealed significantly higher levels of Pro-MMP-2, total MMP-2, and TIMP-2 in the aneurysm's posterior parts (mean Pro-MMP-2 200.52 arbitrary units (AU) versus 161.12 AU, p = 0.007 ; mean total MMP-2 235.22 AU versus 193.68 AU, p = 0.002 ; mean TIMP-2 26.90 ng/ml versus 25.36 ng/ml, p = 0.009 ), whereas the other proteins did not differ significantly within the aortic wall. Thus, MMPs are distributed more heterogeneously within the aortic wall of aTAAs associated with BAV than in those associated with TAV, which is a new aspect for understanding the underlying pathogenesis. This heterogeneous protein level distribution might be attributable to differences in the underlying pathogenesis, especially hemodynamics. This result is important for further studies as it will be essential to specify the location of samples to ensure data comparability regarding the main goals of understanding the pathogenesis of aTAA, optimizing treatments, and establishing a screening method for its potentially deadly complications.